Scalable synthesis of 3-Ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one: an important building block of the antidiabetic drug glimepiride - Chavan, Subhash P.; Pawar, Ambaji A.; Patil, Niteen B.; Kadam, Appasaheb L.; Shinde, Shrikrishna S. (Synthesis-Stuttgart, 2020)
A four-step, practical, and easily scalable synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one, an important building block of the antidiabetic drug glimepiride, has been accomplished. Key features are the synthesis of 3-methyl-4-hydroxy-2-butenolide in water and triflic acid mediated N-benzyl lactam N-deprotection. The main advantages of this process are the scalable synthetic route and decreased number of reaction steps, which paves the way for the industrial-scale synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one.
Keywords: antidiabetic drug; Butenolide; glimepiride; lactams; scalable synthesis

Practical synthesis of 5-hydroxy-2(5H)-furanone from furan - Subhash P. Chavan; Appasaheb L. Kadam (Results in Chemistry, 2021)
A simple, efficient and scalable method for the synthesis of 5-hydroxy-2(5H)-furanone from furan has been developed on a multigram scale. Oxidation of furan has been performed using oxone as the sole oxidant and water as a solvent, which makes this protocol practical and thus industrially applicable.
Keywords: 5-Hydroxy-2(5)-furanone; Furan oxidation; On-water reaction; Oxone; scalable synthesis

Scalable mechanochemical synthesis of beta-ketoenamine-linked covalent organic frameworks for methane storage - Asokan, Kiran; Patil, Manoj Krishnat; Mukherjee, Shatabdi Porel; Sukumaran, Santhosh Babu; Nandakumar, T. (Chemistry-An Asian Journal, 2022)
In the current scenario of increased pollution and releasing toxic gases by burning petroleum products, switching to natural gas is more promising for reducing CO2 emissions and air pollutants. Hence, research on Liquefied Natural Gas and Compressed Natural Gas is gaining more value. However, natural gas primarily consists of CH4, which has less energy density than conventional fuels. Interestingly, since the C-H ratio of CH4 gas is 1 : 4, it is easily combustible, gives less carbon footprint, and reduces unburnt hydrocarbon pollution. Hence, research on storing and transporting CH4 has utmost importance, and porous materials are one of the suitable candidates for storing CH4. Herein we report the scalable synthesis of highly porous and crystalline covalent organic frameworks for storing CH4 at room temperature and pressure. Two COFs, namely, Tp-Azo and Tp-Azo-BD(Me)(2), synthesized in 1 kg at similar to 45 g batch scale using a Planetary mixer, displayed a maximum BET surface area of around 3345 m(2)/g, and 2342 m(2)/g and CH4 storage of 174.10 cc/cc and 151 cc/cc, respectively. A comparison of the CH4 sorption of Tp-Azo and Tp-Azo-BD(Me)(2) COFs synthesized in different batches has a variation of only +/- 5 cc/cc and shows the consistency in bulk scale synthesis of COFs. The cyclic equilibrium CH4 adsorption studies showed the COFs are stable with consistent CH4 adsorption and desorption cycles. The present study is a step towards the scalable mechanochemical synthesis of COFs for gas storage applications.
Keywords: CH4 storage; COF; porous material; scalable synthesis

MOFite: a high-density lithiophilic and scalable metal-organic framework anode for rechargeable lithium-ion battery - Gaber, Safa; Mohammed, Abdul Khayum; Javaregowda, Bharathkumar H.; Martinez, Jose Ignacio; Sanchez, Pilar Pena; Gandara, Felipe; Krishnamoorthy, Kothandam; Shetty, Dinesh (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2024)
Keywords: conjugated MOF; Energy storage; lithium ion battery; Metal-organic framework; scalable synthesis